Detailed phenotyping reveals diverse and highly skewed neutrophil subsets in both the blood and airways during active tuberculosis infection - Nhamoyebonde, Shepherd; Chambers, Mark; Ndlovu, Lerato; Karim, Farina; Mazibuko, Matilda; Mhlane, Zoey; Madziwa, Lindiwe; Moosa, Yunus; Moodley, Sashen; Hoque, Monjurul; Leslie, Alasdair (Frontiers in Immunology, 2024)
Introduction Neutrophils play a complex and important role in the immunopathology of TB. Data suggest they are protective during early infection but become a main driver of immunopathology if infection progresses to active disease. Neutrophils are now recognized to exist in functionally diverse states, but little work has been done on how neutrophil states or subsets are skewed in TB disease. Methods To address this, we carried out comprehensive phenotyping by flow cytometry of neutrophils in the blood and airways of individuals with active pulmonary TB with and without HIV co-infection recruited in Durban, South Africa. Results Active TB was associated with a profound skewing of neutrophils in the blood toward phenotypes associated with activation and apoptosis, reduced phagocytosis, reverse transmigration, and immune regulation. This skewing was also apparently in airway neutrophils, particularly the regulatory subsets expressing PDL-1 and LOX-1. HIV co-infection did not impact neutrophil subsets in the blood but was associated with a phenotypic change in the airways and a reduction in key neutrophil functional proteins cathelicidin and arginase 1. Discussion Active TB is associated with profound skewing of blood and airway neutrophils and suggests multiple mechanisms by which neutrophils may exacerbate the immunopathology of TB. These data indicate potential avenues for reducing neutrophil-mediated lung pathology at the point of diagnosis.